2004
DOI: 10.1023/b:pham.0000045236.60029.cb
|View full text |Cite
|
Sign up to set email alerts
|

The Cohesive-Adhesive Balances in Dry Powder Inhaler Formulations II: Influence on Fine Particle Delivery Characteristics

Abstract: The use of the colloid Atomic Force Microscrope (AFM) technique in combination with the cohesive-adhesive balance (CAB) system provides a novel preformulation tool for investigating the likely behavior of a dry powder formulation and a possible means of interpreting the possible de-aggregation and dispersion mechanisms of carrier-based formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 8 publications
2
73
0
Order By: Relevance
“…Fine particle lactose added as carrier material improved the fluidisation as shown by a shift in the CAB ratio. The study further demonstrated that not only the disaggregation and deposition of the drug itself but also the stability during manufacturing and handling are affected by the CAB ratio within the system (Begat et al, 2004b).…”
Section: Cohesive Adhesive Balance (Cab)mentioning
confidence: 79%
See 1 more Smart Citation
“…Fine particle lactose added as carrier material improved the fluidisation as shown by a shift in the CAB ratio. The study further demonstrated that not only the disaggregation and deposition of the drug itself but also the stability during manufacturing and handling are affected by the CAB ratio within the system (Begat et al, 2004b).…”
Section: Cohesive Adhesive Balance (Cab)mentioning
confidence: 79%
“…The plot shows whether a system is dominated by adhesive or cohesive forces which is important for the development of DPI formulations as agglomeration and segregation, and therefore the fluidisation and dispersion properties of the powder, are affected by the CAB ratio (Begat et al, 2004b). Begat et al (2004a) made use of the colloid probe technique to observe the CAB ratio in DPI formulations of salbutamol sulphate and budesonide with the carrier material lactose.…”
Section: Cohesive Adhesive Balance (Cab)mentioning
confidence: 99%
“…In contrast, however, the effect of the API particle size on in vitro aerosolization performance was not so obvious. In DPI formulation systems, API surface interfacial properties are known to affect drug product performance (13,17,29,30). Traditionally, the surface interfacial properties of APIs have been measured indirectly through measurement of amorphous content or surface free energy (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Particle size, particle morphology, surface roughness and interfacial chemistry of the API and carrier particles have been shown to play a key role in determining these interfacial interactions (9)(10)(11)(12)(13)(14). Whilst the surface and interfacial properties of the API are known to be critical in controlling product performance of DPI products, the primary property characterized for the API component of DPI formulations remains to be the particle size.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation